1998
DOI: 10.1029/98jc01915
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of biogenic and anthropogenic ocean surface films by the multifrequency/multipolarization SIR-C/X-SAR

Abstract: Results from the analyses of several spaceborne imaging radar-C/X-band synthetic aperture radar (SIR-C/X-SAR) images are presented, which were acquired during the two SIR-C/X-SAR missions in April and October 1994 by the L-, C-, and X-band multipolarization SAR aboard the space shuttle Endeavour. The images showing natural (biogenic) surface slicks as well as man-made (anthropogenic) mineral oil spills were analyzed with the aim to study whether or not active radar techniques can be applied to discriminating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 6 publications
4
43
0
Order By: Relevance
“…For clean water, these latter coefficients can be written as [8] (4.6a) and (4.6b) respectively, wherein is the water density; [N s m] is the water dynamic viscosity [8], [32], [38]; and is a dimensionless coefficient equal to about unity, its exact value being unavailable. Simulation results (see Section VI) suggest a value equal to 1.15.…”
Section: Oil Slick Influence On Ocean Surface Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For clean water, these latter coefficients can be written as [8] (4.6a) and (4.6b) respectively, wherein is the water density; [N s m] is the water dynamic viscosity [8], [32], [38]; and is a dimensionless coefficient equal to about unity, its exact value being unavailable. Simulation results (see Section VI) suggest a value equal to 1.15.…”
Section: Oil Slick Influence On Ocean Surface Propertiesmentioning
confidence: 99%
“…By using a simple energy balance equation, in equilibrium conditions we can write [8], [32], [38], [39] (4.1a) (4.1b) wherein subscripts and refer to clean water and to oil slick, respectively. In (4.1), and are the wind input terms; are the nonlinear interaction input terms; and and are the dissipation terms due to viscosity and to breaking waves, respectively.…”
Section: Oil Slick Influence On Ocean Surface Propertiesmentioning
confidence: 99%
“…wave damping, e.g., the reduction of the wind friction velocity [Gade, 1996;Gade et al, 1998a, c; Wismann er ai., i998], the reduction of wave breaking, and the modification of nonlinear wave-wave interactions in the presence of surface films [Alpers and Hiihnerfuss, 1989;Gade et al, 1998b].…”
mentioning
confidence: 99%
“…Several researchers reported that the oil-water backscatter contrast decreases as the radar wavelength increases (Neville et al, 1984;Wismann et al, 1998;Gade et al, 1998). Though some studies show that there is no real difference between horizontal (HH) and vertical (VV) polarization for oil spill detection (Wismann et al, 1998), there is agreement in the literature that VV polarized images provide a better oil-water contrast than either HH or HV polarized images for the C-band (Neville et al, 1984;Singh, 1987;Masuko, 1995;Wismann et al, 1998).…”
Section: Sar Imaging Of Oil Spillsmentioning
confidence: 99%